2017
DOI: 10.1177/1687814017720082
|View full text |Cite
|
Sign up to set email alerts
|

The study of leakage of circular arc–involute–circular arc gear pump

Abstract: In this article, the flow rate and leakage of circular arc-involute-circular arc gear pumps were investigated. Models of transverse and radial leakage patterns of the pump were also developed. The leakage characteristics were studied under different outlet pressures and rotational speeds. The observed results show that leakage decreases and volumetric efficiency increases with an increase in the rotational speed. Contrarily, the leakage increases and efficiency decreases as the outlet pressure increases. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The infinitesimal radial force, tangential force, and axial force (dFr, dFt, and dFz, respectively) are given as follows 12,13 where ex, ey, ez are the unit normal vectors and p^ is the pressure between the high-pressure zone and the low-pressure zone. The unit normal vector can be obtained from where x0(i)', y0(i)' is the first derivative of x0(i), …”
Section: Calculation Of Radial Forcementioning
confidence: 99%
“…The infinitesimal radial force, tangential force, and axial force (dFr, dFt, and dFz, respectively) are given as follows 12,13 where ex, ey, ez are the unit normal vectors and p^ is the pressure between the high-pressure zone and the low-pressure zone. The unit normal vector can be obtained from where x0(i)', y0(i)' is the first derivative of x0(i), …”
Section: Calculation Of Radial Forcementioning
confidence: 99%
“…It was concluded that the time variation of the pressure angle and the gear backlash may lead to a chaotic motion and change the tooth impact status. Another type of studies involved the investigation of the effect of eccentricity P r e p r i n t V e r s i o n on the leakage of circular arc involute circular arc gear pumps was undertaken by Zhou et al [15]. Characteristics of the leakage were studied under different operating conditions such as outlet pressure and rotational speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Wahab [11] used a simple orifice equation to predict the leakage flow rate at different inlet/outlet pressure differences. The effect of eccentricity on leakages was assessed in [12]. Strasser [13] used a movingdeforming grid approach in a commercial computational CFD solver, ANSYS Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Castilla [15] has studied the flow in a suction chamber using a Lagrangian-Eulerian (ALE) formulation. Zhou [12] introduced the mathematical model for the description of the flow rate and leakages in a circular arc gear pump.…”
Section: Introductionmentioning
confidence: 99%